Evaluation Management In The Computer-Based National Examination (UNBK) Case Study At Al-Fudlola' Porong Vocational School, Sidoarjo - Shofi, Millatus; Zuhriya , Latifatu (FATAWA: Jurnal Pendidikan Agama Islam, 2024)
This research aims to describe: (1) Planning for computer-based national exams, (2) Implementation of computer-based national exams (UNBK), (3) Evaluation of computer-based national exams (UNBK) at Al-Fudlola' Porong Vocational School, Sidoarjo. This research is descriptive research with a qualitative approach, the subjects of this research are the proctors of Al-Fudlola' Porong Vocational School, school principals, teachers, research location at Al-Fudlola' Vocational School, Porong sub-district, Sidoarjo district, data collection methods are interviews, observation and documentation, Data validity testing was carried out by triangulating sources and techniques, data analysis using Miles and Huberman data analysis techniques. The research results show the following: Planning includes socialization activities (UNBK), school data collection, infrastructure verification, school determination, and schedule determination (UNBK). Implementation includes pre-examination activities, carrying out official tests, and processing student work results. Evaluation of the occurrence of technical obstacles at Al-Fudlola Vocational School, power outages, lack of space for the school server room, school server computer specifications not by the requirements criteria (UNBK), there are students taking follow-up (UNBK). Students' mental health is disturbed because it is made mandatory in implementing (UNBK). Evaluate solving the problem of technical obstacles, and how to overcome them: providing a backup electrical power supply from a UPS (Uninterruptible Power Supply), remodeling the reading room into a special room for the school server, procuring and repairing computer server hardware devices, registering to take follow-up exams. Non-technical problems carry out routine coaching by holding computer-based national exam (UNBK) exercises for students.